An Analysis of English Word Stress Error Made by First-Year English Department Students - Tina Mulyaningsih; Andrian Nuriza Johan; Sri Widodo (Dinasti Research, 2026)
Word stress is an important suprasegmental feature that affects speech intelligibility and effective oral communication. However, many Indonesian EFL learners still experience difficulties in producing correct English word stress patterns. This study aimed to identify the types and frequency of word stress errors made by first-year students of the English Language Education Study Program at Muhammadiyah University of Purworejo when pronouncing English trisyllabic words. A descriptive qualitative design supported by simple quantitative analysis was employed. The participants were 17 first-year students selected through purposive sampling. Data were collected through a pronunciation test consisting of 20 trisyllabic English words. The students’ pronunciations were recorded and phonetically transcribed. The data were analyzed by comparing the students’ pronunciations with standard English word stress patterns, identifying and classifying the errors into lack of stress, misplaced stress, and overstress, and calculating the frequency and percentage of each error type. The findings showed that, out of 340 pronunciation tokens, 178 (52%) were pronounced correctly, while 162 (48%) contained word stress errors. The highest error rates were found in the words relaxing, election, development, and occasion (76.47%). Three types of errors were identified: lack of stress (49.38%), misplaced stress (42.59%), and overstress (8.02%). These findings indicate that students still face difficulties in producing correct English word stress and require more focused pronunciation instruction and practice.